KARAKTERISASI POLIMER KONDUKTIF POLIPIROL BERPENGISI SERBUK BAN UNTUK MENDETEKSI KONDUKTIVITAS MINYAK - Satriaji Sudigdo, Rizky Dharmawan, Hamidah Harahap (Universitas Sumatera Utara, 2014)
Conductive polymer sensor based polypyrrole (ppy) and tire dust and 1,4-methyl-pyrrolidinone was made by using polymerization process. The polymerization process was prepared at temperature 100°C in boiling water for 30 minutes. Conductive polymer sensor is undergone several type of analysis including electrical conductivity, Scanning Electron Microscopy (SEM), Fourier Transform Infrared (FTIR),and X-Ray Diffraction (XRD). The test used some kind of oil (palm oil,corn oil, diesel, and engine oil). The conductivity test result shows that sensor-4 (contain 20 phr of tire dust) in 80°C at 30 minutes had the highest conductivity. Scanning Electron Microscopy result shows the rough surface and well dispersed of tire dust in polypyrrole/tire dust blends. The XRD analysis shows the Face Centered Cubic (FCC) crystallographic structure of the sensor. The oil conductivity test shows that the corn oil is more reactive than others.